Nuclear Mechanics in the Fission Yeast - Paola Gallardo; Ramón R. Barrales; Rafael R. Daga; Silvia Salas-Pino (Cells, 2019)
In eukaryotic cells, the organization of the genome within the nucleus requires the nuclear envelope (NE) and its associated proteins. The nucleus is subjected to mechanical forces produced by the cytoskeleton. The physical properties of the NE and the linkage of chromatin in compacted conformation at sites of cytoskeleton contacts seem to be key for withstanding nuclear mechanical stress. Mechanical perturbations of the nucleus normally occur during nuclear positioning and migration. In addition, cell contraction or expansion occurring for instance during cell migration or upon changes in osmotic conditions also result innuclear mechanical stress. Recent studies in Schizosaccharomyces pombe (fission yeast) have revealed unexpected functions of cytoplasmic microtubules in nuclear architecture and chromosome behavior, and have pointed to NE-chromatin tethers as protective elements during nuclear mechanics. Here, we review and discuss how fission yeast cells can be used to understand principles underlying the dynamic interplay between genome organization and function and the effect of forces applied to the nucleus by the microtubule cytoskeleton.